2022
DOI: 10.1186/s10194-022-01496-8
|View full text |Cite
|
Sign up to set email alerts
|

A c-Fos activation map in nitroglycerin/levcromakalim-induced models of migraine

Abstract: Background Chronic migraine is a common and highly disabling disorder. Functional MRI has indicated that abnormal brain region activation is linked with chronic migraine. Drugs targeting the calcitonin gene-related peptide (CGRP) or its receptor have been reported to be efficient for treating chronic migraine. The CGRP signaling was also shared in two types of chronic migraine models (CMMs). However, it remains unclear whether the activation of specific brain regions could contribute to persist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 53 publications
3
13
0
Order By: Relevance
“…Of note, in contrast to frequent reports implicating ventral posterolateral (VPL) nucleus and ventral posteromedial (VPM) nucleus of the thalamus in migraine (70,71) and pain processing (13,15) we observed no increase in c-fos expression in either the VPL or VPM. Consistent with our results in this PTH model, previous c-fos based neural activity mapping in migraine models (72,73) similarly reported c-fos increases in SpVc and SSp. However, neither study reported changes in the NAc and therefore this may represent a unique area activated by mTBI induced PTH.…”
Section: Discussionsupporting
confidence: 93%
“…Of note, in contrast to frequent reports implicating ventral posterolateral (VPL) nucleus and ventral posteromedial (VPM) nucleus of the thalamus in migraine (70,71) and pain processing (13,15) we observed no increase in c-fos expression in either the VPL or VPM. Consistent with our results in this PTH model, previous c-fos based neural activity mapping in migraine models (72,73) similarly reported c-fos increases in SpVc and SSp. However, neither study reported changes in the NAc and therefore this may represent a unique area activated by mTBI induced PTH.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies with LEV-induced chronic migraine model adopted the 2nd hour as the testing time for LEV post-treatment responses. This may be the reason why lower thresholds were not consistently observed during the establishment of chronic migraine model in these studies (38,50,51). We observed a similar degree of threshold reduction in both LEV and NTG groups, however in the LEV group, decay time of threshold was signi cantly shorter in comparison to NTG group.…”
Section: Discussionmentioning
confidence: 60%
“…1 C-E). C-Fos is thought to be a biomarker of neuronal activation responding to nociceptive stimuli, which is highly correlated with migraine pathogenesis [ 43 ]. Our results indicated that the protein expression of c-Fos in the TNC was upregulated significantly in the NTG group when compared with the saline group ( p < 0.001; Fig.…”
Section: Resultsmentioning
confidence: 99%